Pengaruh Konseling Kelompok Dengan Metode Modelling The Way Untuk Meningkatkan Keterampilan Berbicara Pada Santri - Risna Lestari; Suryati suryati; Lena Marianti (Journal of Society Counseling, 2023)
The thesis entitled “The Influence of Group Counseling Using The Way Modelling Method to Improve Speaking Skills In Santri”. The background of this that many santri do not have the courage to speak in public, speaking skill is one aspect of language skills that is productive, meaning that is an ability that a person conveys ideas, thoughts skills of Ahlul Quro’ boarding school students and to determine the effect of group counseling using the modeling the way method to inprove speaking skills of Ahlul Quro’ boarding school students. The methodology in this study uses a quantitative research type, this research is an experimental research while the design used is a one group pretest[1]posttest experimental design. The population in this study amounted to 33 students, to take samples using a purposive sampling technique totaling 9 students from the entire population. The instruments contained in this study are observation, questionnaires, and documentation. This research uses paired sample t test analysis. The results of the study before being given treatment, the results of the pretest pictures of the level of speaking skills of the students in the counseling group were in the medium category with a presentation of 46%, after being given treatment the results of the posttest pictures of the speaking skills of the students in the counseling group were in the medium category with a presentation of 54%. Then the result of the sign value (2-tailed) is smaller than 0.005 (0.00<0.005) wich shows H0 is rejected an Ha is acception. ><0.005) wich shows H0 is rejected an Ha is acception.